Carbon dioxide sequestration of iron ore mining waste under low-reaction condition of a direct mineral carbonation process - Mohd Kusin, Faradiella; Syed Hasan, Sharifah Nur Munirah; M. Molahid, Verma Loretta; Mohamat Yusuff, Ferdaus; Jusop, Shamsuddin (Springer Nature, 2022)
Mining waste that is rich in iron-, calcium- and magnesium-bearing minerals can be a potential feedstock for sequestering CO2 by mineral carbonation. This study highlights the utilization of iron ore mining waste in sequestering CO2 under low-reaction condition of a mineral carbonation process. Alkaline iron mining waste was used as feedstock for aqueous mineral carbonation and was subjected to mineralogical, chemical, and thermal analyses. A carbonation experiment was performed at ambient CO2 pressure, temperature of 80 °C at 1-h exposure time under the influence of pH (8–12) and particle size (< 38–75 µm). The mine waste contains Fe-oxides of magnetite and hematite, Ca-silicates of anorthite and wollastonite and Ca-Mg-silicates of diopside, which corresponds to 72.62% (Fe2O3), 5.82% (CaO), and 2.74% (MgO). Fe and Ca carbonation efficiencies were increased when particle size was reduced to < 38 µm and pH increased to 12. Multi-stage mineral transformation was observed from thermogravimetric analysis between temperature of 30 and 1000 °C. Derivative mass losses of carbonated products were assigned to four stages between 30–150 °C (dehydration), 150–350 °C (iron dehydroxylation), 350–700 °C (Fe carbonate decomposition), and 700–1000 °C (Ca carbonate decomposition). Peaks of mass losses were attributed to ferric iron reduction to magnetite between 662 and 670 °C, siderite decarbonization between 485 and 513 °C, aragonite decarbonization between 753 and 767 °C, and calcite decarbonization between 798 and 943 °C. A 48% higher carbonation rate was observed in carbonated products compared to raw sample. Production of carbonates was evidenced from XRD analysis showing the presence of siderite, aragonite, calcite, and traces of Fe carbonates, and about 33.13–49.81 g CO2/kg of waste has been sequestered from the process. Therefore, it has been shown that iron mining waste can be a feasible feedstock for mineral carbonation in view of waste restoration and CO2 emission reduction.